A Model for Reconfiguration of Multi-Modal Real-Time Systems under Energy Constraints - Nassife, Riad; Camponogara, Eduardo; Lima, George (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2011)
The problem of maximizing quality of service (QoS) of real-time systems subject to both schedulability and energy constraints is addressed. A discrete system consisting of tasks with multiple operating modes, and which can be executed by the processor at different frequency/voltage levels, is considered. Although the system reconfiguration scheme assumes the earliest deadline first (EDF) policy and soft real-time tasks, it can be extended to other scheduling policies and handle hard real-time tasks. The described solution is suitable for adaptive real-time embedded systems which require energy savings associated to QoS. Despite being NP-Hard, the reconfiguration problem can be solved with a mixed-integer linear-programing solver sufficiently fast.